Aggregation‐induced emission: Red and near‐infrared organic light‐emitting diodes. (27th August 2021) - Tu, Liangjing; Xie, Yujun; Li, Zhen; Tang, Benzhong
Abstract: Red and near‐infrared (NIR) organic light‐emitting diodes (OLED) have gained remarkable interest due to their numerous applications. However, the construction of highly emissive emitters is hampered by the energy‐gap law and aggregation‐caused quenching (ACQ) effect. Whereas, aggregation‐induced emission (AIE) materials could avoid the undesirable ACQ effect and emit bright light in aggregated state, which is one class of the most promising materials to fabricate high‐performance OLED with a high external quantum efficiency and low efficiency roll‐off. This review summarizes recent advances in red and NIR OLED with AIE property, including the traditional fluorescence, thermally activated delayed fluorescence, and hybridized local and charge transfer compounds. Meanwhile, the emphasis attention is paid to the molecular design principles, as well as the molecular structure‐photophysical characteristics. We also briefly further outlook the challenges and perspective of red and NIR AIE luminogens. Abstract : In the field of organic light‐emitting diodes (OLED), red and near‐infrared (NIR) emitter with aggregation‐induced emission (AIE) effect can be divided into fluorescence, thermally activated delayed fluorescence (TADF), and hybridized local and charge transfer (HLCT) according to emission mechanism.